PENGARUH BIMBINGAN KARIR TERHADAP MINAT MELANJUTKAN PERGURUAN TINGGI DI SMA NEGERI 3 SEKADAU - Siska, Dominika; Asrori, Asrori; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCareer guidance is guidance given to students to help students in planning, developing and solving career problems to get the best possible adjustments to their future, so that students choose higher education according to their interests, talents and abilities. Therefore, the researcher wants to know more deeply about the influence of career guidance on the interest in continuing higher education in class XI students of SMA Negeri 3 Sekadau Hilir. This study aims to describe whether there is an effect of career guidance on the interest in continuing higher education in students of class XI of SMA Negeri 3 Sekadau Hilir in 2018 Academic Year. The methodology of this study is descriptive method with a quantitative approach. The population of this study was 46 students. Based on the results of data analysis shows that career guidance is categorized as